NEGARA HUKUM DAN PLURALISME AGAMA; TINJAUAN TERHADAP PERLINDUNGAN HAK MINORITAS BERAGAMA DI INDONESIA - Anshar, Sayid; Ifing, Baso (Ensiklopedia Sosial Review, 2025)
Abstract :This study examines the protection of religious minority rights within the framework of state law (rechtsstaat) and religious pluralism in Indonesia. Based on doctrinal research method with legislative, case, conceptual, and historical approaches, this study analyzes legal instruments such as the 1945 Constitution, Law No. 39/1999 on Human Rights, as well as international provisions that guarantee freedom of religion. The results show that although Indonesia has a strong constitutional foundation including Articles 28E and 29 of the 1945 Constitution that prohibit religious discrimination, its implementation still faces serious challenges, such as intolerance, violence, and injustice against minority groups. Religious pluralism, as a pillar of national unity (Bhinneka Tunggal Ika), requires strengthening interfaith dialogue and inclusive law enforcement. This study also examines the Islamic perspective through the Medina Charter, which emphasizes freedom of religion without coercion. Research recommendations include improving the effectiveness of law enforcement, public education on tolerance, and policy reforms to ensure equal rights for all religious groups. The findings highlight the importance of harmonization between legal norms and social practices to realize justice for religious minorities in Indonesia.Keywords: Rule of law, religious pluralism, minority rights, freedom of religion, 1945 Constitution